Determinants of Mortality in Children under Five Years of Age with Severe Acute Malnutrition Admitted to the Yalgado Ouédraogo Teaching Hospital (Burkina Faso) (International Journal of Child Health and Nutrition, 2016)
Background: To determine critical factors associated with severely malnourished children under five this case-control study was conducted.Methods: The data of a total of 433 children aged 0-59 months and admitted to the Hospital Yalgado Ouedraogo, (CHU – YO) between January 31, 2009 to January 31, 2013, were included in the analysis: 72 for the case group and 361 for the control group. Clinical and treatment records were accessed and data were analyzed.Results: For clinical signs, determinants of mortality were diarrhea [OR = 4.6; (95%CI 2.6-8.2], anorexia [OR = 2.7; (95%CI 1.4-5.0] and hepatomegaly [OR = 2.6; (95%CI 1.4-4.8]. For infections, determinants of mortality were pediatric HIV/AIDS [OR = 10.9; (95%CI 5.6-21.5] and digestive illnesses [OR = 5.1 (95%CI 2.8-9.4)]. Regarding the complications of malnutrition, determinants of mortality were severe dehydration [OR = 16.4 (95%CI 8.0-33.5)], skin lesions [OR = 14.3 (95%CI 6.4 -31.9)], heart failure [OR = 6.8 (95%CI 2.5-19.0)] and severe anemia [OR = 3.2(95%CI 1.4-7.1)]. For biochemical indicators, low serum sodium [OR = 0.7(95%CI 0.5-1.0)] and potassium levels [OR = 0.9(95%CI 0.9-1.0)] were the critical factors. In addition the risk of death was associated with low value of MUAC [OR = 0.9 (95% CI 0.8-0.9)].Conclusions: The risk of death of children with severe acute malnutrition varies according to different factors studied.